Detectable anthropogenic influence on summer compound hot events over China from 1965 to 2014 - Wang, Xiaoxin; Lang, Xianmei; Jiang, Dabang (Environmental research letters, 2022)
Compared with independent hot days or nights, compound hot extremes have more adverse effects on society. In this study, hot extremes are categorized into three types: independent hot days, independent hot nights and compound hot events combining daytime and nighttime hot extremes based on daily maximum and minimum temperatures. Using observations from the gridded dataset CN05.1 and experiments undertaken with 22 Coupled Model Intercomparison Project Phase 6 (CMIP6) models, we analyze the observed changes in summer hot extremes and compare them with model simulations over China between 1961 and 2014 and then conduct detection and attribution analyses of changes in compound hot events between 1965 and 2014 utilizing an optimal fingerprinting method. The results show that clear upward trends in the frequency and intensity of the three types of hot extremes are observed over China, with the largest trend occurring in hot nights for frequency and in compound hot events for intensity. The CMIP6 multimodel mean responses to all forcings agree well with the observed changes in the frequency and intensity of the three types of hot extremes. Anthropogenic (ANT) forcing can be robustly detected and separated from the response to natural (NAT) forcing in the frequency and intensity trends of compound hot events over China, and the attributable contribution of ANT forcing is estimated to be much larger than that of NAT forcing. Further analyses on the model responses to NAT, greenhouse gas (GHG) and ANT aerosol (AER) forcings indicate that GHG forcing is detectable in the observed increased frequency of compound hot events. By contrast, NAT and AER forcings cannot be detected, and their effects on the observed changes in compound hot events over China are generally negligible.